Synthesis and antitubercular evaluation of new 1,2,3-triazole derivatives of carbohydrates - Santos, Juliana Alves dos; Corrales, Roberta Cristina Novaes Reis; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Dias, Rafael Mafra de Paula; Silva, Adilson David da (Mediterranean Journal of Chemistry, 2012)
We reported in this work the preparation of novel 1,4-disubstituted-1,2,3-triazoles derivatives from Dglucose and D-fructose and their in vitro antibacterial activity against Mycobacterium tuberculosis were evaluated. The chemical synthesis was performed based on the 1,3-dipolar cycloaddition reaction, and antimicrobial activity was determined based on Resazurin Microtiter Assay against Mycobacterium. None of the triazole glycoconjugates tested showed activity against these microorganisms.
Keywords: Carbohydrate; Glycoconjugates; 1,2,3-triazole; Antitubercular activity